PENINGKATAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN PENDIDIKAN PANCASILA MENGGUNAKAN MODEL COOPERATIVE LEARNING TIPE GROUP INVESTIGATION (GI) BERBANTUAN FLASH CARD DI KELAS V SDN 16 PADANG BESI (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the results of field observations, namely the low learning outcomes of students in Pancasila Education learning for grade V at SDN 16 Padang Besi. These problems are indicated by students not working freely and tending to be silent, students participating less in making decisions, ineffective communication between students. In addition, the learning process is still teacher-centered so that students feel bored and tired in the learning process. This study aims to describe the improvement in student learning outcomes in Pancasila Education learning using the cooperative learning model of group investigation type assisted by flash cards. The type of research used is Classroom Action Research (CAR) using qualitative and quantitative approaches. This research was conducted in two cycles, with research procedures consisting of planning, implementation, observation, and reflection stages. The research data obtained are related to student learning outcomes in Pancasila Education learning using the cooperative learning model of group investigation type assisted by flash cards. Data collection techniques are in the form of tests and non-tests. The subjects of this study were the class teacher as observer, the researcher as practitioner, and 26 fifth grade students of SDN 16 Padang Besi. The results showed an increase in student learning outcomes. The average learning outcome of the attitude aspect of cycle I was 69.92, then increased in cycle II to 84.97, the average learning outcome of the knowledge aspect of cycle I was 84.52, then increased in cycle II to 87.5, the average learning outcome of the skills aspect of cycle I was 73.55, then increased in cycle II to 84.61. Thus, it can be concluded that the cooperative learning model of group investigation type assisted by flash cards can improve student learning outcomes in Pancasila Education learning in fifth grade of SDN 16 Padang Besi.